9x-7=-3x+29

Simple and best practice solution for 9x-7=-3x+29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-7=-3x+29 equation:


Simplifying
9x + -7 = -3x + 29

Reorder the terms:
-7 + 9x = -3x + 29

Reorder the terms:
-7 + 9x = 29 + -3x

Solving
-7 + 9x = 29 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-7 + 9x + 3x = 29 + -3x + 3x

Combine like terms: 9x + 3x = 12x
-7 + 12x = 29 + -3x + 3x

Combine like terms: -3x + 3x = 0
-7 + 12x = 29 + 0
-7 + 12x = 29

Add '7' to each side of the equation.
-7 + 7 + 12x = 29 + 7

Combine like terms: -7 + 7 = 0
0 + 12x = 29 + 7
12x = 29 + 7

Combine like terms: 29 + 7 = 36
12x = 36

Divide each side by '12'.
x = 3

Simplifying
x = 3

See similar equations:

| -1.4121-(1-2.4)= | | 4+(2)(3)= | | 4(2+3)= | | 7x-14=-3x+6 | | 3(x-1)(x+1)=9 | | 7+(1)(-2)= | | 7(1)+(-2)= | | 7(1+-2)= | | 3(2x-1)=4(x+2) | | 7(7x-2)=49x-14 | | -5+2(4)= | | -5(2)+4= | | y-4=-2/3x | | -5(1-2n)=15 | | -5(2+4)= | | 9x+7=-5+7x+16 | | -3(t+3)=15 | | 47-15=4(x-6) | | 70+5y-32=17y-11-5y | | 2+(-3)(4)= | | (36m-9mn=45n)/9 | | k^2+2k+-60=0 | | -4(p+5)= | | 4(2x+9)=-7x-24 | | 2(-3+4)= | | 50+3x= | | 5=-5a+2a | | 4(k+0.5)=2k+k+6 | | 1000x+2500=-4000 | | 4*x^2*(x^2-1)=17*x^2-25 | | 17-3(2x-7)=7x-3(2x-1)equation | | 4*x^2*(x-1)=17*x^2-25 |

Equations solver categories